2018
DOI: 10.3390/en11082127
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Characteristics Investigation of the Internal Combustion Engine Cooling-Combustion System Using Thermal Boundary Dynamic Coupling Method and Experimental Verification

Abstract: The engine cooling system must be able to match up with the stable operating conditions so as to guarantee the engine performance. On the working cycle level, however, the dynamic thermo-state of engines has not been considered in the cooling strategy. Besides, the frequent over-cooling boiling inside the gallery changes the cooling capacity constantly. It is necessary to study the coupling effect caused by the interaction of cooling flow and in-cylinder combustion so as to provide details of the dynamic contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Considering that each system is suitable for different working conditions, this paper analyzes the performance according to the actual working conditions of vehicles. Figure 19 shows that the time percentage of engine speed and torque in different ranges when the vehicle is running in cities and highways [27]. Combined with the net power of three systems under different working conditions, the comprehensive net power of each system under different environmental temperatures under urban and high-speed working conditions can be obtained, as shown in Figure 20.…”
Section: System Performance Under Actual Conditionsmentioning
confidence: 99%
“…Considering that each system is suitable for different working conditions, this paper analyzes the performance according to the actual working conditions of vehicles. Figure 19 shows that the time percentage of engine speed and torque in different ranges when the vehicle is running in cities and highways [27]. Combined with the net power of three systems under different working conditions, the comprehensive net power of each system under different environmental temperatures under urban and high-speed working conditions can be obtained, as shown in Figure 20.…”
Section: System Performance Under Actual Conditionsmentioning
confidence: 99%
“…The coolant temperature gradient in the jacket was assumed constant, and was represented by the arithmetic mean value of the engine inlet and outlet temperatures. To establish the convection heat transfer equations, the Hohenberg convection heat transfer model was applied to determine the heat transfer coefficients, specifically and [34]. The convection heat transfer equations of the coolant are defined as…”
Section: Engine Internal Thermal Transmission Modelmentioning
confidence: 99%
“…Many technologies have been developed for improving the efficiency of engines, such as engine downsizing [2][3][4], the Atkinson or Miller cycle [4][5][6], gasoline direct injection (GDI) [7][8][9], the homogeneous charge compression ignition (HCCI) [10][11][12][13][14], reduction of exhaust energy loss [15,16] or heat loss [17][18][19][20], electrical or precisely controlled cooling systems [20][21][22], and combustion phase control [23]. Cesare et al [1] reported that engine downsizing concepts, such as turbocharging combined with GDI, have contributed to the recent improvements of ICEs.…”
Section: Introductionmentioning
confidence: 99%
“…Legros et al [16] compared various waste heat treatment technologies, such as Rankine cycles, thermoelectric generators, and turbo compounding, and achieved a fuel reduction of up to 6%. Zhang et al [20] proposed a dynamic control of cooling systems and achieved low heat loss. Gao et al [23] used the in-cylinder pressure sensor to calculate the combustion phase and indicated mean effective pressure (IMEP) for maximum fuel efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation